Morphological aspects of Culex quinquefasciatus salivary glands - Sais, Tiago da Cunha; Moraes, Rosa Maria de; Ribolla, Paulo E.; De Bianchi, Antonio G.; Marinotti, Osvaldo; Bijovsky, A. Tania (Elsevier, 2003)
The salivary glands of Culex quinquefasciatus female mosquitoes are paired organs composed of two lateral lobes with proximal and distal secretory portions, and a medial lobe. All portions comprise a simple epithelium that surrounds a salivary duct. In the apical portion of the medial lobe, non-secretory cells strongly resemble cells involved in ion and water transport. The general architecture of the secretory portions is similar between lobes. The appearance of the secretory material and the morphological aspect of the apical cell membrane are the most distinctive features among the three secretory portions. Cells in the lateral proximal lobe display thin membrane projections extending into a translucent and finely filamentous secretory product. At the lateral distal portion, the apical cell membrane forms an intricate meshwork that encloses a dark secretory product. Medial lobe secretory cells also contain secretory cavities surrounded by intracytoplasmic vesicles, all containing a very dark and uniform product. Scattered cells holding numerous vacuoles, some of them containing a small and electron-dense granule eccentrically located and resembling those of the diffuse endocrine system, are frequently observed in the periphery of all secretory portions. Immunofluorescence assays revealed that the distal portion of the lateral lobes contains apyrase, an enzyme putatively responsible for platelet aggregation inhibition, diffusely distributed in the cell cytoplasm. © 2003 Elsevier Ltd. All rights reserved.
Keywords: Apyrase; Culex quinquefasciatus; Mosquito; Salivary gland; Ultrastructure; apyrase; apical membrane; cell vacuole; cytoplasm; diffusion; electron dense granule; epithelium; granule cell; immunofluorescence test; ion transport; morphological trait; nonhuman; salivary gland; salivary gland duct; secretory cell; thrombocyte aggregation inhibition; water transport; Culex pipiens quinquefasciatus